The tour of the West Indian cricketers, August and September, 1886 : 'a memory' - Fyte, L. R. (Canoe P. KingstonJM, 2006)
Details the West Indies Cricket Team's tour of Canada and the United States in 1886 and speaks to the Canadian and American beginning of the West Indian cricket culture.